2022
DOI: 10.12688/f1000research.26025.2
|View full text |Cite
|
Sign up to set email alerts
|

Career planning courses increase career readiness of graduate and postdoctoral trainees

Abstract: Background: Given national calls for intentional career development during graduate and post-graduate scientific training, this study assessed career readiness development within the context of academic career courses. The current study evaluated the effects of academic career courses offered at two institutions that were specifically designed to increase career awareness, interest, and career-related confidence among doctoral students and postdoctoral fellows. Methods: Participants enrolled in a career course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…However, no significant association was found between the absence of career planning courses and a high percentage of uncertainty. It is to be noted that multiple international studies have reported that career planning courses do increase career readiness (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant association was found between the absence of career planning courses and a high percentage of uncertainty. It is to be noted that multiple international studies have reported that career planning courses do increase career readiness (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Such decisions are entirely up to the college body to decide, hence through this study, we could find other possible ways a college environment affects career choice. One other way a college affects a student's career is through career counseling programs and such programs have been proved to be useful for career success and planning by multiple studies (10)(11)(12). With increasing stress about professional examinations and the introduction of the national Licensing Exam (NLE), we hope to use this study to understand and help medical students of Pakistan who are uncertain about their future.…”
Section: Introductionmentioning
confidence: 99%
“…Many programs focus on academic careers (e.g., The Preparing Future Faculty Program) and development for non-academic career paths can be limited [8]. This, despite the fact that only 15% of postdocs secure tenure-track faculty positions [2,9].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Numerous challenges exist with current professional development opportunities for postdocs offered at academic institutions and/or through professional societies. Many programs focus on academic careers (e.g., The Preparing Future Faculty Program) and development for non-academic career paths can be limited [8]. This, despite the fact that only 15% of postdocs secure tenure-track faculty positions [2, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous challenges exist with current professional development opportunities for postdocs offered at academic institutions and/or through professional societies. Many programs focus on academic careers (e.g., The Preparing Future Faculty Program) and development for non-academic career paths can be limited [ 8 , 9 ]. This, despite the fact that only 15% of postdocs secure tenure-track faculty positions [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%